Penerapan Metode SMA (Single Moving Average) dalam Penggunaan Bahan Baku Kue dan Roti pada Momy’s Cake And Bread - Nurhidayanti Nurhidayanti; Neni Mulyani; Yori Apridonal (LPPM STMIK Royal Kisaran, 2021)
Abstract: Momy's Cake and Bread is one of the businesses engaged in the bakery and cake food industry that produces various types of bread, and cakes, ranging from Korean garlic bread, toasted brownise and others. All products have the same raw materials such as wheat flour, sugar, eggs, bananas, butter and others. There are times when there is excess raw material, but sometimes it is also lacking, a shortage of raw material supplies that a little will have an impact on the production process stopping which results in losing customers because they cannot meet their needs. Forecasting is a technique that aims to predict what will happen next based on pre-existing data. With this forecasting technique, it can provide predictions so that users can take effective steps that can be taken next. The ingredients to be predicted are wheat flour, sugar, eggs, bananas, coconut, white butter, cocoa, almonds, cocoa powder, vanilla. So that getting the forecast value in July 2021, the results Mean Absolute Deviation (MAD) = 9,5874, Mean Square Error (MSE) = 18225,39162 and Mean Absolute Perentage Error (MAPE) = 30%, will be designed and built using the language PHP and MySQL programming so that it can be accessed using the internet and the system is based on a website. Keyword:Forecasting; Single Moving Average; Cake and Bread Raw Materials; Momy's Cake And Bread. Abstrak: Momy’s Cake and Bread merupakan salah satu usaha yang bergerak di bidang industri makanan roti dan kue yang memproduksi berbagai jenis roti, dan kue, mulai dari roti korean garlic, brownise panggang dan lain-lain. Semua produk memiliki bahan baku yang sama seperti tepung terigu, gula pasir, telur, pisang, mentega dan lain-lain. Ada kalanya bahan baku berlebih, namun terkadang juga kurang, kekurangan persediaan bahan baku yang sedikit akan berdampak pada proses produksi yang berhenti yang berakibat kehilangan pelanggan karena tidak dapat memenuhi kebutuhannya. Peramalan merupakan sebuah teknik yang bertujuan untuk melakukan prediksi mengenai apa yang akan terjadi selanjutnya berdasarkan data-data yang telah ada sebelumnya. Dengan teknik peramalan tersebut dapat memberikan prediksi sehingga penggunanya dapat melakukan langkah-langkah efektif yang dapat dilakukan selanjutnya. Bahan yang akan diramalkan adalah bahan tepung terigu, gula pasir, telur, pisang, kelapa, mentega putih, coklat, kacang almond, coklat bubuk, vanili. Sehingga mendapatkan nilai peramalan pada bulan juli 2021di dapat hasil Mean Absolute Deviation (MAD) = 9,5874, Mean Square Error (MSE) = 18225,39162 dan Mean Absolute Perentage Error (MAPE) = 30%, akan dirancang dan dibangun dengan menggunakan bahasa pemrograman PHP dan MySQL sehingga dapat diakses dengan menggunakan internet dan sistem tersebut berbasis website. Kata Kunci : Peramalan; Single Moving Average; Bahan Baku Kue dan Roti; Momy’s Cake And Bread.